Determinants Of Diarrhea Among Toddlers In Bram Itam Kiri Sub-District Bram Itam Barat Tanjung Jabung District - Andi Subandi; Andy Amir (Lembaga Pengembangan Kinerja Dosen, 2022)
Background : Diarrhea is still the leading cause of morbidity and mortality in the world. According to data from the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) in 2013 diarrhea is the second leading cause of death in children under five. The purpose of the study was to determine the relationship between mother's education level, occupation, income, mother's knowledge, and latrine ownership with the incidence of diarrhea in children under five in Bram Itam Kiri Village.Methods : Using a cross sectional approach with a population of 166 mothers, the number of samples was 68 respondents. The sampling technique was carried out using simple random sampling. Data were collected using a questionnaire sheet and analyzed univariate and bivariate using chi square analysis.Results : The level of education in the low category is 48.5%, employment in the unemployed category is 58.9%, income in the low category is 70.6%, knowledge in the poor category is 83.8%, latrine ownership in the category does not meet terms of 61.8%. Bivariate results of education level (0.003), mother's occupation (1,000), family income (0.019), knowledge (0.028), and latrine ownership (0.002) with the incidence of diarrhea in children under five.Conclusion : There is a relationship between the level of education, family income, knowledge, and ownership of latrines, and there is no relationship between the mother's occupation and the incidence of diarrhea in children under five.